Optical soliton solutions for the higher-order dispersive cubic-quintic nonlinear Schrodinger equation - İnç, Mustafa; Yusuf, Abdullahi; Aliyu, Aliyu Isa; Baleanu, Dumitru (Academic Press Ltd- Elsevier Science Ltd, 2017)
In this paper, we analyze new optical soliton solutions to the higher-order dispersive cubic-quintic nonlinear Schrodinger equation (NLSE) using three integration schemes. The schemes used in this paper are modified tanh-coth (MTC), extended Jacobi elliptic function expansion (EJEF), and two variable (G '/G,1/G)-expansion methods. We obtain new solutions that to the best of our knowledge do not exist previously. The obtained solutions includes bright, dark, combined bright-dark, singular as well as periodic waves solitons. The obtained solutions may be used to explain and understand the physical nature of the wave spreads in the most dispersive optical medium. Some interesting figures for the physical interpretation of the obtained solutions are also presented. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: NLSE; MTC method; EJEF method; G '/G, 1/G-expansion method